Analisis Kualitas Air dan Kandungan Logam Berat Timbal (PB) pada Air Laut di Perairan Pelabuhan Kelas II Jayapura Papua - Marsia Isa Bwefar; Irja Sepriyanto Jenmau; Irwandi Yogo Suaka; Frans Deminggus; Yohannes Rahail (Jurnal Impresi Indonesia, 2025)
This study aims to analyze water quality and heavy metal lead (Pb) content in the waters of Class II Port of Jayapura, Papua. Increased port and industrial activities in coastal areas can contribute to environmental pollution, including heavy metal contamination that impacts marine ecosystems and the health of coastal communities. This research employed a descriptive method with water sampling at 2 stations, each consisting of 3 sub-stations using purposive sampling technique. Seawater samples were analyzed at the Chemistry Education Laboratory of Cenderawasih University using Atomic Absorption Spectrophotometry (AAS). Water quality parameters measured included temperature, pH, Dissolved Oxygen (DO), transparency, and salinity. The results showed that water quality parameters were within safe ranges according to quality standards, with temperature ranging from 30.2-32.5°C, pH 6.54-7.60, DO 5.45-8.55 mg/l, transparency 3.20-3.57 meters, and salinity 30-34. However, the heavy metal lead (Pb) content in seawater ranged from 0.115-0.141 mg/l, which exceeded the established quality standard limit of 0.05 mg/l based on Government Regulation Number 22 of 2021 and Minister of Environment Decree Number 51 of 2004. This research indicates that port activities such as loading and unloading of goods, ship washing, fuel usage, fuel spillage, and use of ship coating paint can affect the level of lead in the waters. Special attention and strict supervision of port activities are required to minimize heavy metal pollution in the waters of Jayapura Port.